Valuable effect of Manuka Honey in increasing the printability and chondrogenic potential of a naturally derived bioink. (March 2022) - Scalzone, Annachiara; Cerqueni, Giorgia; Bonifacio, Maria A.; Pistillo, Michele; Cometa, Stefania; Belmonte, Monica Mattioli; Wang, Xiao N.; Dalgarno, Kenny; Ferreira, Ana M.; De Giglio, Elvira; Gentile, Piergiorgio
Abstract: Hydrogel-based bioinks are the main formulations used for Articular Cartilage (AC) regeneration due to their similarity to chondral tissue in terms of morphological and mechanical properties. However, the main challenge is to design and formulate bioinks able to allow reproducible additive manufacturing and fulfil the biological needs for the required tissue. In our work, we investigated an innovative Manuka honey (MH)-loaded photocurable gellan gum methacrylated (GGMA) bioink, encapsulating mesenchymal stem cells differentiated in chondrocytes (MSCs-C), to generate 3D bioprinted construct for AC studies. We demonstrated the beneficial effect of MH incorporation on the bioink printability, leading to the obtainment of a more homogenous filament extrusion and therefore a better printing resolution. Also, GGMA-MH formulation showed higher viscoelastic properties, presenting complex modulus G∗ values of ∼1042 ​Pa, compared to ∼730 ​Pa of GGMA. Finally, MH-enriched bioink induced a higher expression of chondrogenic markers col2a1 (14-fold), sox9 (3-fold) and acan (4-fold) and AC ECM main element production (proteoglycans and collagen). Graphical abstract: Image 1